BMM1533 workbook: strength of materials 1 - Siti Rabiatull Aisha, Idris; M., Ishak; Aiman, Mohd Halil (Penerbit UMP, 2017)
This workbook consists of four chapters which are Stress and Strain under Axial Loading, Torsion,Pure Bending and Analysis and Design of Beams for Bending.There are brief, yet compact notes for students to understand better and at the same time easy to remember. In this workbook, student will learn on how to solve the engineering problems in the simplest way. It will also guide the students to answer the question in unique ways